KADAR ANTOSIANIN, TOTAL FENOL DAN SIFAT SENSORIS TEPUNG TAPE BERAS HITAM BERDASARKAN VARIASI METODE PENGOLAHAN DAN KONSENTRASI RAGI - Marini firia dewi; nurhidajah nurhidajah; Siti aminah (Universitas Muhammadiyah Semarang, 2019)
Black rice tapai flour is a product that can familiarizing black rice to general public. The purpose of this research was to determine the best formula of black rice tapai flour based on anthosianin content, total phenol and characteristic sensory analization results. The research design used was a Completely Randomized Design (RAL) factorial with two factors, the processing method and yeast concentration. Each factor consists of three levels. Processing methods are steamed, team and boiling black rice using rice cooker and the concentration of yeast is 1%, 2% and 3% so that nine treatment combinations are repeated three times. The results showed that the black rice tapai flour with tim processing method + 2% yeast concentration is the best formula for tapai flour. Proximate value of black rice tapai flour with tim processing method + 2% yeast concentration is 11.3% water content, 7.74% protein, 4.63% fat, 19.21% fiber, 2.51% ash content and carbohydrate 54.61%.